Evolutionary Tinkering of the Mandibular Canal Linked to Convergent Regression of Teeth in Placental Mammals - Ferreira-Cardoso, Sérgio; Delsuc, Frédéric; Hautier, Lionel (Current Biology, 2019)
International audience Loss or reduction of teeth has occurred independently in all major clades of mammals [1]. This process is associated with specialized diets, such as myrmecophagy and filter feeding [2, 3], and led to an extensive rearrangement of the mandibular anatomy. The mandibular canal enables lower jaw innervation through the passage of the inferior alveolar nerve (IAN) [4, 5]. In order to innervate teeth, the IAN projects ascending branches directly through tooth roots [5, 6], bone trabeculae [6], or bone canaliculi (i.e., dorsal canaliculi) [7]. Here, we used micro-computed tomography (μ-CT) scans of mandibles, from eight myrmecophagous species with reduced dentition and 21 non-myrmecophages, to investigate the evolutionary fate of dental innervation structures following convergent tooth regression in mammals. Our observations provide strong evidence for a link between the presence of tooth loci and the development of dorsal canaliculi. Interestingly, toothless anteaters present dorsal canaliculi and preserve intact tooth innervation, while equally toothless pangolins do not. We show that the internal mandibular morphology of anteaters has a closer resemblance to that of baleen whales [7] than to pangolins. This is despite masticatory apparatus resemblances that have made anteaters and pangolins a textbook example of convergent evolution. Our results suggest that early tooth loci innervation [8] is required for maintaining the dorsal innervation of the mandible and underlines the dorsal canaliculi sensorial role in the context of mediolateral mandibular movements. This study presents a unique example of convergent redeployment of the tooth developmental pathway to a strictly sensorial function following tooth regression in anteaters and baleen whales.